5-fluorocytosine resistance is associated with hypermutation and alterations in capsule biosynthesis in Cryptococcus - R. Blake Billmyre (Nature Portfolio, 2020)
The authors show that resistance to the antifungal 5-fluorocytosine in Cryptococcus deuterogattii is acquired more frequently in isolates with elevated mutation rate, and is associated with alterations in capsule biosynthesis and nucleotide metabolism.